2016
DOI: 10.1128/aem.03452-15
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Type IX Secretion System in Capnocytophaga ochracea Gliding Motility and Biofilm Formation

Abstract: dCapnocytophaga ochracea is a Gram-negative, rod-shaped bacterium that demonstrates gliding motility when cultured on solid agar surfaces. C. ochracea possesses the ability to form biofilms; however, factors involved in biofilm formation by this bacterium are unclear. A type IX secretion system (T9SS) in Flavobacterium johnsoniae was shown to be involved in the transport of proteins (e.g., several adhesins) to the cell surface. Genes orthologous to those encoding T9SS proteins in F. johnsoniae have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…), and more recent work has shown that Capnocytophaga ochracea, another Gram‐negative bacterium involved in periodontal disease utilizes its gliding motility system to facilitate the formation of biofilms (Kita et al . ). While little to no work has been done on the gliding motility system of F. columnare , in the terrestrial F. johnsoniae a broad number of studies have described gliding motility and the T9SS mechanisms (McBride & Nakane ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), and more recent work has shown that Capnocytophaga ochracea, another Gram‐negative bacterium involved in periodontal disease utilizes its gliding motility system to facilitate the formation of biofilms (Kita et al . ). While little to no work has been done on the gliding motility system of F. columnare , in the terrestrial F. johnsoniae a broad number of studies have described gliding motility and the T9SS mechanisms (McBride & Nakane ).…”
Section: Discussionmentioning
confidence: 97%
“…Upon activation of an iron-depleted LV-359-01 phenotype, a survival phenotype may prevent resources from going towards biofilm formation even when adequate iron is added into the system. Interestingly, the depletion of iron has been shown to inhibit P. aeruginosa biofilms through the disruption of quorum sensing and twitching motility systems (Cai et al 2010), and more recent work has shown that Capnocytophaga ochracea, another Gram-negative bacterium involved in periodontal disease utilizes its gliding motility system to facilitate the formation of biofilms (Kita et al 2016). While little to no work has been done on the gliding motility system of F. columnare, in the terrestrial F. johnsoniae a broad number of studies have described gliding motility and the T9SS mechanisms (McBride & Nakane 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of T9SSs in the nutrition, physiology, motility, and virulence of members of the phylum Bacteroidetes has been demonstrated (1,3,19,36,(38)(39)(40). Most of the proteins with easily predicted functions that are secreted by T9SSs have type A CTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Other Bacteroidetes members use the T9SS for the secretion of adhesins required for gliding motility, or enzymes required for supplying carbon, heme and metal sources [5][6][7][8]. P. gingivalis, the main causative agent of periodontal diseases, secretes a plethora of virulence factors at its cell surface, including the gingipains that play an important role in gum infections [9].…”
Section: Introductionmentioning
confidence: 99%